2007
DOI: 10.1152/ajpheart.00163.2007
|View full text |Cite
|
Sign up to set email alerts
|

Aging is associated with myocardial insulin resistance and mitochondrial dysfunction

Abstract: Aging is associated with insulin resistance, often attributable to obesity and inactivity. Recent evidence suggests that skeletal muscle insulin resistance in aging is associated with mitochondrial alterations. Whether this is true of the senescent myocardium is unknown. Twelve young (Y, 4 years old) and 12 old (O, 11 years old) dogs, matched for body mass, were instrumented with left-ventricular pressure gauges, aortic and coronary sinus catheters, and flow probes on left circumflex artery. Before surgery, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…We did not observe any effect of age in indexes of Ca 2ϩ -induced MPT in the present study; however, 8-yr-old beagles should be considered middle aged, as the typical life span of this strain is 13.5 Ϯ 0.2 yr (24). A previous study found that healthy 11 Ϯ 2-yr-old male beagles had a decrease in succinate dehydrogenase activity in myocardial tissue homogenates and a qualitative increased vacuolization of mitochondria by visual analysis of electron micrographs compared with 4 Ϯ 1-yr-old animals; however, mitochondrial respiration and MPT were not assessed (3). Future studies should evaluate these parameters in senescent dogs, where greater mitochondrial dysfunction would be expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not observe any effect of age in indexes of Ca 2ϩ -induced MPT in the present study; however, 8-yr-old beagles should be considered middle aged, as the typical life span of this strain is 13.5 Ϯ 0.2 yr (24). A previous study found that healthy 11 Ϯ 2-yr-old male beagles had a decrease in succinate dehydrogenase activity in myocardial tissue homogenates and a qualitative increased vacuolization of mitochondria by visual analysis of electron micrographs compared with 4 Ϯ 1-yr-old animals; however, mitochondrial respiration and MPT were not assessed (3). Future studies should evaluate these parameters in senescent dogs, where greater mitochondrial dysfunction would be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that mitochondrial yield and functional differences between SSM and IFM were qualitatively similar in the LV and RV with responses to aging and aldosterone infusion (Figs. [3][4][5][6][7][8]. The present investigation was not designed to statistically compare the RV with the LV, as this would require a three-way ANOVA (chamber ϫ mitochondrial population ϫ age/treatment group) and thus a much larger sampled size to achieve acceptable statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is associated with whole body and myocardial insulin resistance, independent of obesity and inactivity as shown in a wellcharacterized large-animal model of aging with senescent beagles [22]. Moreover, the senescent myocardium was associated with myocardial insulin resistance and mitochondrial dysfunction.…”
Section: Aging Insulin Resistance and Heart Failure: A Unifying Hypothmentioning
confidence: 93%
“…In fact, in a relevant large animal model of senescent beagles, Shannon et al have demonstrated the magnitude and the mechanism of whole body and myocardial insulin resistance and the cellular mechanisms involved [22]. Myocardial insulin resistance is specifically associated with mitochondrial structural and functional abnormalities that predispose to insulin resistance.…”
Section: Aging Insulin Resistance and Diastolic Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation